The influence of IQ, emotional and spiritual perceptions on sports participation in an effort to improve physical health - Andri Gemaini; Yanuar Kiram; Anton Komaini; Özgür Eken; Hardzikrillah Jalius; Endang Sepdanius; Muhamad Sazeli Rifki; Novadri Ayubi (Universidad de Murcia, 2024)
Article accepted. The article will be published here soon. Pending final quality checks.